2018
DOI: 10.1186/s12985-018-1018-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and sequence analysis of equid herpesviruses from the respiratory tract of Polish horses

Abstract: BackgroundEquid herpesviruses (EHVs) are widespread in equine populations worldwide. While the infection with equine α-herpesviruses (EHV-1 and EHV-4) has been linked to several clinical outcomes, the pathogenic potential for equine γ-herpesviruses (EHV-2 and EHV-5) is still unclear. The objective of the current study was to determine the prevalence of infection with EHVs among Polish horses, to investigate factors associated with EHV infections among horses sampled, and to determine genetic variability within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 56 publications
9
38
0
2
Order By: Relevance
“…More recently in other countries, prevalence observed in nasal swab samples from Poland were EHV-2 (77.2%, 417/540), EHV-4 (0.4%, 2/540), and EHV-5 (47%, 254/540) in horses [19], and in nasal swab and blood samples from Ethiopia they were EHV-1 (3.4%, 4/119), EHV-2 (25.2%, 30/119), EHV-4 (7.6%, 9/119), and EHV-5 (28.6%, 34/119) in horses with respiratory disease or EHV-2 (7.9%, 8/101) and EHV-5 (17.8%, 18/101) in healthy horses [20]. In a previous Korean study, EHV-1 (5.6%, 5/89) and -4 (7.9%, 7/89) by real-time PCR and EHV-5 (39%, 35/89) by conventional PCR were detected only from nasal swabs from horses suffering from respiratory diseases in 2008 [12], and EHV-2 (2.3%, 10/430) and -5 (2.6%, 11/430) by conventional PCR only were detected in genital swabs from healthy horses recently [13].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…More recently in other countries, prevalence observed in nasal swab samples from Poland were EHV-2 (77.2%, 417/540), EHV-4 (0.4%, 2/540), and EHV-5 (47%, 254/540) in horses [19], and in nasal swab and blood samples from Ethiopia they were EHV-1 (3.4%, 4/119), EHV-2 (25.2%, 30/119), EHV-4 (7.6%, 9/119), and EHV-5 (28.6%, 34/119) in horses with respiratory disease or EHV-2 (7.9%, 8/101) and EHV-5 (17.8%, 18/101) in healthy horses [20]. In a previous Korean study, EHV-1 (5.6%, 5/89) and -4 (7.9%, 7/89) by real-time PCR and EHV-5 (39%, 35/89) by conventional PCR were detected only from nasal swabs from horses suffering from respiratory diseases in 2008 [12], and EHV-2 (2.3%, 10/430) and -5 (2.6%, 11/430) by conventional PCR only were detected in genital swabs from healthy horses recently [13].…”
Section: Discussionmentioning
confidence: 86%
“…Results revealed a higher prevalence of EHV-2 (41.7%) than that of EHV-5 (21.7%) in the blood. Previous studies from Hungary, Sweden, the UK [21], New Zealand [16], Poland [19], and Iceland [22] have also reported that EHV-2 is more frequently detected than EHV-5. However, in this study, lung tissue and nasal swab samples presented with a higher prevalence of EHV-5 (18.7% and 11.2%, respectively) than that of EHV-2 (13.4% and 5.5%, respectively); this finding corresponds with reports from Australia [10], Ethiopia [20], Korea [13], and Turkey [18].…”
Section: Discussionmentioning
confidence: 93%
“…All samples developed viral cytopathic effect within 2 to 6 days post inoculation. The identity of the viral isolates was confirmed by EHV-1 specific PCR [29,30].…”
Section: Virus Isolationmentioning
confidence: 99%
“…Following a low-speed centrifugation, supernatants from tissues from the same fetus were pooled and stored at − 80°C. DNA was extracted from 200 μL of each pooled supernatant using QIAamp DNA Mini Kit (Qiagen, Germany) according to the manufacturer's recommendations and tested for the presence of EHV-1 and EHV-4 DNA using previously published primers from the conserved region of glycoprotein B [29,30]. Positive (EHV-1 438/77 and EHV-4 405/76, American Type Culture Collection) and negative (water) controls were included in each PCR run.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…This is the first report of EHV-2 and EHV-5 DNA in the upper respiratory tracts of asymptomatic adult horses from Brazil. Gammaherpesviruses have been detected in horse populations in several countries worldwide [1,15,18,19]. In South America, EHV-2 was successfully isolated from cells cultured from symptomatic horses in Argentina [20,21].…”
Section: Resultsmentioning
confidence: 99%